Determinan Perilaku Kunjungan Antenatal Care di Puskesmas Bojongsari Kota Depok Tahun 2021 - Aurelia Indah Qurota A'yun; Astrid Novita; Ernita Prima Noviyani (SIMFISIS Jurnal Kebidanan Indonesia, 2021)
Introduction: The behavior of antenatal care visits is the action of pregnant women who carry out pregnancy checks from the first trimester to the third trimester. Objective: To determine the relationship between health service facilities, health promotion, health care support, and the quality of health services on the behavior of antenatal care visits at the Bojongsari Health Center, Depok City in 2021. Methods: This type of research used a quantitative analytic survey using a cross-sectional approach. The population in this study was 141 pregnant women in the third trimester. The sampling technique used was the Lemeshow formula with purposive sampling. The number of respondents was 103 third-trimester pregnant women. The types of data used are primary and secondary data with univariate and bivariate analysis. Results: Pregnant women with poor antenatal care visits were 58 pregnant women (56.3%). Conclusion: There is a relationship between the variables of service facilities (OR = 27.773), health promotion (OR = 19.213), health care support (OR = 22.519), and the quality of health services (OR = 26.057) on the behavior of antenatal care visits at the Bojongsari Health Center, Depok City. 2021.